2014
DOI: 10.1177/0022466913517554
|View full text |Cite
|
Sign up to set email alerts
|

Using an iPad Application to Promote Early Literacy Development in Young Children With Disabilities

Abstract: This investigation evaluated the effects of using an iPad application to teach young children with developmental delays to receptively identify initial phonemes through 0-to 5-s constant time delay procedures in the context of a multiple-probe design across three sets of behaviors and replicated across three students. The dependent variable was the percentage of unprompted correct receptive identification responses for target phonemes during instruction and probes. All students mastered their target phonemes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 20 publications
(34 reference statements)
1
45
0
Order By: Relevance
“…After a post-test on alphabet knowledge, matching, and number concepts, they reported that use of the iPad-supported learning in the areas of alphabet knowledge and number concepts. Zhen et al (2015) looked at the effects of using an iPad application to teach four young children with disabilities to identify initial phonemes and found that performance was improved and the children enjoyed using the iPad. Chmiliar (2013, 2014), in a series of two pilot studies with preschool children with disabilities, found that young children between the ages of three to five were able to successfully learn to navigate the iPad.…”
Section: Introductionmentioning
confidence: 99%
“…After a post-test on alphabet knowledge, matching, and number concepts, they reported that use of the iPad-supported learning in the areas of alphabet knowledge and number concepts. Zhen et al (2015) looked at the effects of using an iPad application to teach four young children with disabilities to identify initial phonemes and found that performance was improved and the children enjoyed using the iPad. Chmiliar (2013, 2014), in a series of two pilot studies with preschool children with disabilities, found that young children between the ages of three to five were able to successfully learn to navigate the iPad.…”
Section: Introductionmentioning
confidence: 99%
“…First, all 14 studies received 3‐point scores for the first sub‐category (participant description) by providing an operational definition of the participants' disabilities and details such as age, gender and IQ. For the second sub‐category (participant selection), only six studies (Burton et al, ; Chai et al, ; Creech‐Galloway et al, ; Rivera et al, ; Seok et al, ; Spooner et al, ) received 2‐point or 3‐point scores by describing criteria for selecting participants along with reading pre‐assessment data; the other eight studies received 1‐point scores mostly because they lacked data from reading pre‐assessments. With regard to the third sub‐category, setting description, ten studies received 3‐point scores; two studies received 2‐point scores because they provided some features of setting but needed more details such as type of classroom, room arrangement and number of students per teacher.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a study to examine the effects of iPod‐assisted instruction on job‐related tasks (Kellems & Morningstar, ), informal interview data with 16‐ to 22‐year‐old students with autism spectrum disorders revealed that, in addition to the usefulness of the devices in completing the task, the students expressed enjoyment, willingness to participate in the task and a positive preference for using an iPod for future work. Similarly, informal interview data in a study by Chai, Vail and Ayres () showed that all K‐2 students with disabilities enjoyed using the touch sound in an iPad application when they were asked to respond during constant time delay session procedures for matching initial phonemes (e.g., choosing the same beginning sound).…”
Section: Tablet‐assisted Instruction Approaches For Students With Dismentioning
confidence: 91%
See 1 more Smart Citation
“…The iPad has been shown to: increase the academic engagement of students who have language-based disabilities (Cumming and Draper Rodriguez, 2013); increase time on task of elementary-level students who experience challenging behaviour during independent academic activities (Flower, 2014); support students with support communication skills in English Language Learners (Demski, 2011); promote literacy and social goals in students with multiple and complex needs by providing an multi-modal method of developing and sharing personal stories (Kucirkova, Messer, Critten, et al, 2014); teach young children with developmental delays to receptively identify initial phonemes, a foundational early literacy skill (Chai, Vail and Ayres, 2015); and offer modelling for students with Autism Spectrum Disorder and developmental disabilities (Burton, Anderson, Prater, et al, 2013;Hammond, Whatley, Ayres, et al, 2010).…”
Section: Why the Ipad?mentioning
confidence: 99%